Sie sind auf Seite 1von 5

# COMSATS INSTITUTE OF INFORMATION TECHNOLOGY, LAHORE

## Signals and Systems (Fall 2010)

Instructor: M. A. Siddique

SOLUTION QUIZ 1

Question 1:
Make a labelled sketch of z(t) = 2x(t − 2) + 3y(t − 1)
where x(t) and y(t) are as given below:

(a) (b)

Solution 1:
Let z1 (t) = 2x(t − 2) and z2 (t) = 3y(t − 1). Then z(t) = z1 (t) + z2 (t)
z1 (t) and z2 (t) are as shown below:

(a) (b)

(c)

1
Question 2:
Make a labelled sketch of: x(2t + 1)

Solution 2:

There is no strict way of how to approach this problem. It’s too simple!
I would focus on the ‘transition1 ’ points in the graph of x(t) i.e. where the slope of the lines or the
curve flow chages abrupty, and at zero-crossings. In this case, these would be the points that lie at
t = −1, 0, 1, 2, 3, 4

The function f (t) = x(2t + 1) has the argument A = 2t + 1. I would check at which points of t would the
argument be equal to the ‘transtion points’ e.g.

## 2t + 1 = −1 ⇒ t = −1 and we have f (−1) = 0

1
2t + 1 = 0 ⇒ t = − and we have f (0) = 1
2
2t + 1 = 1 ⇒ t = 0 and we have f (1) = 1
1
2t + 1 = 2 ⇒ t = and we have f (2) = 0
2
2t + 1 = 3 ⇒ t = 1 and we have f (3) = −1
3
2t + 1 = 4 ⇒ t = and we have f (4) = 0
2
Hence you get the graph as in figure 1.

## 1 It’s note a formal term!

2
Figure 1: Solution of question 2: x(2t + 1)

Question 3:
Consider the following three systems:

1. A full wave rectifier whose output is the modulus of the input: y(t) =| x(t) |
2. A modulator whose carrier frequency is ωc : y(t) = x(t)cos(wct)
3. A system whose output is the average of its input over preceding time T:

ˆt
1
y(t) = x(t)dt
T
t−T

Determine whether each of the systems is: i) Linear ii) Time-invariant iii) Causal

Solution 3:

1. Full-wave recitifier

## • Checking for linearity:

Consider an input x1 (t). The corresponding output is y1 (t) =| x1 (t) |. Considering another input
x2 (t), the corresponding output is y1 (t) =| x1 (t) |. Now considering a linear combination of x1 (t)
and x2 (t) such as
x3 (t) = ax1 (t) + bx2 (t)
where a and b are constants. The corresponding output is then:

y3 (t) =| x3 (t) |=| ax1 (t) + bx2 (t) |6= a | x1 (t) | +b | x2 (t) |

## ⇒ y3 (t) 6= ay1 (t) + by2 (t)

Hence, the system in non-linear.
• Checking for time-invariance:
Let x1 (t) be an input to the system. Then the corresponding output is y1 (t) =| x1 (t) |. Considering
a delayed version of the input, x2 (t) = x1 (t − t0 ), the output is

## Delaying the output y1 (t), we get y1 (t − t0 ) =| x1 (t − t0 ) |. Therefore,

⇒ y2 (t) = y1 (t − t0 )

It means that a delayed input is leading to a correspondingly delayed output. Hence, time-invariant.

3
• Checking for Causality
The system relies only on the current value of the input. No future value is used. Hence, Causal.

2. Modulator

## • Checking for linearity:

Consider an input x1 (t). The corresponding output is y1 (t) = x1 (t)cos(wct). Considering another
input x2 (t), the corresponding output is y2 (t) = x2 (t)cos(wct). Now considering a linear combina-
tion of x1 (t) and x2 (t) such as
x3 (t) = ax1 (t) + bx2 (t)
where a and b are constants. The corresponding output is then:

## y3 (t) = ax1 (t) · cos(wct) + bx2 (t) · cos(wct)

y3 (t) = ay1 (t) + by2 (t)
The system is therefore, Linear.
• Checking for time-invariance:

Let x1 (t) be an input to the system. Then the corresponding output is y1 (t) = x1 (t)cos(wct). Con-
sidering a delayed version of the input, x2 (t) = x1 (t − t0 ), the output is

## Delaying the output y1 (t), we get y1 (t − t0 ) = x1 (t − t0 )cos{wc (t − t0 )}. Therefore, in general,

⇒ y2 (t) 6= y1 (t − t0 )

## • Checking for Causality

The system relies only on the current value of the input. No future value is used. Hence, Causal.

3. Averaging system:

## Consider an input x1 (t). The corresponding output is

ˆt
1
y1 (t) = x1 (t)dt
T
t−T

## Consider another input x2 (t). The corresponding output is

ˆt
1
y2 (t) = x2 (t)dt
T
t−T

## where a and b are constants. The corresponding output is then:

ˆt
1
y3 (t) = x3 (t)dt
T
t−T

4
ˆt ˆt
1 1
⇒ y3 (t) = a · x2 (t)dt + b · x2 (t)dt
T T
t−T t−T

ˆt ˆt
1 1
y3 (t) = a · x2 (t)dt + b · x2 (t)dt
T T
t−T t−T

## Hence the system in Linear.

• Checking for Time-Invariance
´t
Let x1 (t) be an input to the system. Then the corresponding output is y1 (t) = T1 t−T x1 (t)dt. Con-
sidering a delayed version of the input, x2 (t) = x1 (t − t0 ), the corresponding output is

ˆt ˆt
1 1
y2 (t) = x2 (t)dt = x1 (t − t0 )dt
T T
t−T t−T

which is equal to
ˆt
1
y2 (t) = x1 (t − t0 )dt = y1 (t − t0 )
T
t−T

## We have x2 (t) = x1 (t − t0 ), and the corresponding output y2 (t) = y1 (t − t0 ). Hence time-invariant,

i.e. a delayed input is leading to a correspondingly delayed output.
• Checking for Causality
´t
The system is defined by y(t) = T1 t−T x(t)dt. It implies that the output relies on the current and
the previous values of time over the duration T. No future value of the input is used. Hence, the
system in Causal.